2022
DOI: 10.11591/ijere.v11i1.21914
|View full text |Cite
|
Sign up to set email alerts
|

Group investigation model to improve interpersonal skills

Abstract: <p><span>This study aimed to prove the effectiveness of the application of the group investigation learning model in improving students' interpersonal skills. The sample of this study was 116 students, which was determined by a simple random sampling technique. This experimental research used pre-test post-test Control Group Design. Data were obtained by direct observation of the interpersonal skills of students during the learning process. Final observation score of interpersonal skills is 0.026 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
2
3
0
2
Order By: Relevance
“…The analysis results on the second data set indicated that the problem-solving skills of students who attended learning using the GI learning method also increased significantly. This finding is consistent with the results reported by previous studies that GI enhances students' problem-solving skills [20], [22]. Combining problem-solving and cooperative learning strategies promotes students' high-order thinking skills through collaborative interaction [46].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The analysis results on the second data set indicated that the problem-solving skills of students who attended learning using the GI learning method also increased significantly. This finding is consistent with the results reported by previous studies that GI enhances students' problem-solving skills [20], [22]. Combining problem-solving and cooperative learning strategies promotes students' high-order thinking skills through collaborative interaction [46].…”
Section: Discussionsupporting
confidence: 93%
“…This finding reinforces the theory describing that creativity can be improved by associating the initial knowledge (through Remap) with the strategy for cultivating cognitive skills (GI) [34]. Studies investigating GI learning models have been massively carried out [20], [23], but this study offered a different context as it used online learning.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The group investigation learning paradigm requires many steps to be completed, including grouping, planning, inquiry, arranging, presenting, and assessment (Ainiyah et al, 2022). At the grouping stage, students are divided into investigative groups.…”
Section: B Action Implementation Stage (Acting)mentioning
confidence: 99%
“…Low social skills can cause a person to be selfish, indifferent, and lacking in empathy. This can give rise to various social problems, such as aggressive behavior, coercion of will, destruction, intergroup conflict, and fighting [ 52 ]. In fact, studies by Barlinska, Lalak and Szuster, [ 53 ] Martínez, Rodríguez-Hidalgo, and Zych [ 2 ] suggest that having well-developed social skills is protective against bullying, including cyberbullying and victimization.…”
Section: Introductionmentioning
confidence: 99%